Islamic Banking Profitability: Roles Played by Internal and External Banking Factors - Mohd Aziz, N. I. (Universiti Sains Islam Malaysia, 2024)
Due to the uncertainties and slowdown in the global economy, Islamic banking is facing challenges that will affect its performance and profitability. Poor performances include high levels of credit risk, poor quality loans, limited or inadequate capitalization, operational efficiencies and high level of credit risk will influence the profit of banks. The idea of this paper is to examine hoe internal and external factors affect the profitability of Islamic banks. This will be seen on how performance through bank size, asset quality, GDP, inflation and money supply attempts to address the banks' profitability. 11 samples of banks with six year financial data are chosen to be analyzed in this research. The result is obtained by applying panel data analysis, using the probability sample. It is expected that the findings of this study will show that the variety of internal and external factors will lead to banks profitability. If the Islamic banks fully understand and able to determine the strength factors, will enhance the institutions' profitability. Therefore, policy makers, financial analyst and investors may benefit from this research as the findings could be used as a guideline for them in analyzing the factors affecting the success of Islamic banks, thus will contribute to the high growth rate in these banks that are currently operating in Malaysia. A future research should include internal and external factors that will affect the profitability of banks such as liquidity risk, bank operational efficiency and capital efficiency.